2022
DOI: 10.1371/journal.pmed.1004039
|View full text |Cite
|
Sign up to set email alerts
|

Associations between moderate alcohol consumption, brain iron, and cognition in UK Biobank participants: Observational and mendelian randomization analyses

Abstract: Background Brain iron deposition has been linked to several neurodegenerative conditions and reported in alcohol dependence. Whether iron accumulation occurs in moderate drinkers is unknown. Our objectives were to investigate evidence in support of causal relationships between alcohol consumption and brain iron levels and to examine whether higher brain iron represents a potential pathway to alcohol-related cognitive deficits. Methods and findings Observational associations between brain iron markers and alc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 81 publications
1
30
0
Order By: Relevance
“…Gout patients had higher incidence of probable essential tremor, previously linked to cerebellar atrophy [27,28]. Associations with markers of higher iron in basal ganglia with hyperuricaemia mirror findings in aging, Alzheimer’s and Parkinson’s diseases [29,30], and recently alcohol consumption [31]. Our MR findings provide support for causal relationships underlying the associations.…”
Section: Discussionsupporting
confidence: 72%
“…Gout patients had higher incidence of probable essential tremor, previously linked to cerebellar atrophy [27,28]. Associations with markers of higher iron in basal ganglia with hyperuricaemia mirror findings in aging, Alzheimer’s and Parkinson’s diseases [29,30], and recently alcohol consumption [31]. Our MR findings provide support for causal relationships underlying the associations.…”
Section: Discussionsupporting
confidence: 72%
“…However, recent studies suggest that no level of alcohol consumption is safe in humans. These studies show that even moderate alcohol consumption has been associated with ROS generation, hypertension, stroke, vascular alterations in the peripheral and central nervous systems, cognitive decline, and more ( Gill et al, 1986 ; Roerecke et al, 2017 ; Cho et al, 2022 ; Ohlrogge et al, 2022 ; Topiwala et al, 2022 ).…”
Section: Extrinsic Influences On Vascular Smooth Muscle Cell Dysfunctionmentioning
confidence: 83%
“…Daily smoking is associated with many adverse health effects across multiple organ systems and adding the brain to the list of organs adversely effected by smoking is biologically plausible. For the last criterion, analogical evidence, there is similar evidence of alcohol associated with adverse consequences on the brain (28,29). A recent study investigated the causal relationship between smoking and alcohol and subcortical brain volume variations and concluded that smoking and heavy alcohol consumption can causally reduce subcortical brain volume (30).…”
Section: Discussionmentioning
confidence: 99%